2004
DOI: 10.1007/s00167-003-0486-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anterior cruciate ligament reconstruction in male and female athletes using the patellar tendon and hamstring autografts

Abstract: Despite the higher incidence of anterior cruciate ligament (ACL) injuries in female than in male athletes few authors have studied the effects of gender on the outcome of ACL reconstruction. This prospective study compared the results of ACL reconstruction using the patellar tendon and hamstring techniques in men and women. We prospectively followed 80 comparable athletes (46 males, 32 females) from a population of 287 patients operated on at our institution for ACL reconstruction using either patellar tendon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
88
5
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(112 citation statements)
references
References 23 publications
16
88
5
3
Order By: Relevance
“…Barret et al have suggested that generalized ligamentous laxity, which is more frequent in females, contributes to increased graft laxity [4]. This is in line with the findings of Corry and Gobbi [6,12]. They found a significant increased laxity in females operated with a autologous hamstring graft.…”
Section: Discussionsupporting
confidence: 81%
“…Barret et al have suggested that generalized ligamentous laxity, which is more frequent in females, contributes to increased graft laxity [4]. This is in line with the findings of Corry and Gobbi [6,12]. They found a significant increased laxity in females operated with a autologous hamstring graft.…”
Section: Discussionsupporting
confidence: 81%
“…However, contrary to some previous studies, especially those relating to female patients [8,17], an increase in post-operative knee laxity using ST/ G autografts was not found [6,13,36]. In our opinion, this is an interesting and important finding and indicates that ST/G grafts may be safely used even in young, highly active male athletes.…”
Section: Discussioncontrasting
confidence: 54%
“…We must always plan our surgery according to the type of patient we are presented with; for instance, a double-bundle ACLR may be more appropriate for an athlete of high-contact or impact sport but certainly not for a skeletally immature patient or a patient with important lateral femoral condyle bone bruise [8,38,46,47,49,51]. Furthermore, we must also consider the anthropometric anatomy; thus, a thin light female would not be a good candidate for DB ACLR [13]. There is a considerable learning curve associated with DB ACLR.…”
Section: Discussionmentioning
confidence: 99%